Non-vitamin K antagonist oral anticoagulants (NOACs) in cancer patients with atrial fibrillation - Anetta Undas; Leszek Drabik (Anatolian Journal of Cardiology)
Non-vitamin K antagonist oral anticoagulants (NOACs), or direct oral anticoagulants have not been tested in randomized trials conducted in patients with atrial fibrillation (AF), who had malignant disease. However, their use in cancer patients increases and real-life evidence for their effectiveness and safety in this vulnerable subset of patients is growing. The challenges of the use of NOACs in cancer patients with AF and the current expert opinions on this subject have been summarized in this review article.